Effect of heat distribution and vibration on wider lead frame / Nurfarrahain Nadia Ahmad - Nurfarrahain Nadia, Ahmad (2019)
Adoption of more electronic components in end products, the semiconductor industry is facing a challenge era that requires price management to achieve efficiency, high productivity and excellence with each of the diverse customers. One of the strategies is to enhance the wider of lead frame size for cost down reduction related on material and increase the productivity. However there are two main challenges of wider lead frame implementation which is heat distribution not even and vibration issue that will cause bonding performance no good. Heat distribution uneven is causing warpage due to heating principle at machine. High density unit per lead frame may contribute to warpage and it cannot be avoid. This issue can be improving by design consideration of dimple installation in order to release the material stress after applied heat. For vibration concern, upward floating lead on widen lead frame give potential of finger lead bouncing during bonding process, make the second bond ability become weak. As for future improvement, some modification on die-set stamping required to flatten the finger inner lead and reduce their vibration.